TINJAUAN KETERSEDIAAN SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI DAN KESEHATAN DI SMP NEGERI SE-KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR - Alfi Candra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The availability of facilities and infrastructure for physical education learning in SMP Negeri se-Kecamatan Perhentian Raja Kabupaten Kampar still minimal. The research objective to be achieved is to know whether the sports facilities and infrastructure owned SMP Negeri seKecamatan Perhentian Raja Kabupaten Kampar is good. This type of research is descriptive qualitative data collection techniques in this research is to use a list of matches (checklist). The population of this research is all SMP Negeri se-Kecamatan Perhentian Raja Kabupaten Kampar with two SMP is SMP Negeri 5 and SMP Negeri 6 Perhentian Raja Kampar, with samples of all the population sampled is also called total sampling. Data were analyzed using descriptive statistical techniques. Research results show that the sports facilities and infrastructure owned by 2 SMP Negeri se-Kecamatan Perhentian Raja is SMP Negeri 5 Perhentian Raja Kampar with the results of 56.54% (categorized enough), and SMPN 6 Perhentian Raja Kampar with the results of 39.46% (categorized not good), it can be concluded ahir of the second SMP Negeri se-Kecamatan Perhentian Raja Kabupaten Kampar by the number of 48% Infrastructures poorly categorized sports.